THE ROLE OF PREGNANCY COMPLICATIONS IN CHILDHOOD COMPLICATIONS - Noor Hidayah; Aurora Sinta Sabila; Ashri Maulida Rahmawati; Rusnoto Rusnoto (Universitas Muhammadiyah Kudus, 2024)
Pregnant women at risk If the pregnancy is not treated, the risk of maternal and fetal morbidity and mortality during delivery is 2.8 times. This study analyzes data from the Local Area Monitoring of high-risk pregnancies at the Kaliwungu Public Health Center, Kudus Regency, and emergency delivery by approach observational cohort retrospective among 149 respondents who experienced difficult childbirth (January to March 2023) later observed at the time of delivery until the end of 2023. Statistical test results with Chi-Square showed a result of 0.436a and a p-value of 0.509, which means there is no correlation between pregnancy complications and childbirth complications. The results of this research will make it possible to take data as a whole for one or several years to analyze it statistically based on conditions in the field.